Effect of Different Biomass Levels of Eichhornia crassipes and Pistia stratiotes on Nutrients, Organics, and Heavy Metals Removal from Wastewater - Ajiboye, Adewale V.; Badmos, Babajide; Adelodun, Adedeji A.; Babatola, Josiah O. (Tecno Scientifica Publishing, 2024)
This study investigates the impact of varying biomass levels of Eichhornia crassipes (water hyacinth) and Pistia stratiotes (water lettuce) on the removal efficiency of nutrients, organic matter, and selected heavy metals from paint industry wastewater. The experiment was conducted using different biomass quantities of the aquatic plants to evaluate their phytoremediation capabilities. Changes in physicochemical parameters, nutrients, organic pollutants, and selected heavy metals were monitored over a 14-day period. At the end of week 1, water lettuce (WL) achieved removal efficiencies of 37.16%, 62.94%, and 38.47% for NO₃⁻, PO₄³⁻, and NH₃, respectively. Water hyacinth (WH) achieved removal efficiencies of 45.18%, 61.07%, and 45.86% for NO₃⁻, PO₄³⁻, and NH₃, respectively. Similarly, both plants significantly removed heavy metals, with WH achieving average removal efficiencies of 95.91%, 90.88%, and 67.68% for Cr, Pb, and Cu, respectively. WL achieved the highest average removal efficiencies of 90% and 88.9% for Zn and Cu, respectively. A statistically significant difference was observed among the biomass level treatments and heavy metal removal efficiencies (p < 0.05). The results indicate that both species effectively reduced nutrient, organic pollutant, and heavy metal concentrations, with higher biomass levels showing greater removal efficiencies. WH exhibited slightly better performance in removing all evaluated parameters in the wastewater treatment compared to WL. This study highlights the potential of these aquatic plants for phytoremediation applications in wastewater treatment systems. Optimization of biomass levels and operational conditions could enhance removal efficiencies and make the process more sustainable.